(untitled) (Journal of the College of Basic Education, 2022)
Praise be to Allah، the Lord of the Worlds، and prayers and peace be upon the Most Merciful of the Messengers، our Master Muhammad، his family and companions and those who guided him to the Day of Judgment. God has made me to make it difficult (book of foresight)، and honored to be the focus of my studies: ((The words of differentiation in the book of insight into the door of worship and study)) (The words chosen in the book of purity). I have been in the preparation of the search on the plan and Ali, and three demands، and a conclusion، and a list of sources and references.